Effect of Nutrition on Health of Patients Suffering from Chronic Disease: Impact of Dietary Factors on Chronic Disease Management (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The mechanics of the chronic illness process are better understood, and treatments have beenshown to minimize risk, thanks to a Joint WHOFAO Expert Consultation on Diet, Nutrition, and thePrevention of Chronic Diseases held in Geneva from January 28th to February 1st, 2002. Industrialization,urbanization, economic growth, and market globalization have all contributed to significant dietary andlifestyle shifts, and these shifts have increased over the last decade. The term nutrition refers to theconsumption of food in proportion to one's dietary requirements. The study found that 80.8 of the 401Umrah pilgrims with chronic illnesses were currently taking medication. Type 2 diabetes accounted for41.4 of all illnesses. 206 HCPs at Sligo University Hospital responded to the NUTCOMP survey